2009
DOI: 10.1002/art.24626
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines are associated with radiographic joint damage in rheumatoid arthritis

Abstract: Objective. Obesity protects against radiographic joint damage in rheumatoid arthritis (RA) through poorly defined mechanisms. Adipocytokines are produced in adipose tissue and modulate inflammatory responses and radiographic joint damage in animal models. The purpose of this study was to examine the hypothesis that adipocytokines modulate inflammation and radiographic joint damage in patients with RA.Methods. We compared serum concentrations of leptin, resistin, adiponectin, and visfatin in 167 RA patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
191
2
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(217 citation statements)
references
References 38 publications
17
191
2
7
Order By: Relevance
“…On the contrary to our results, the studies conducted by Forsblad et al 19 , Kassem et al 15 and Rho et al 23 found a significant positive correlation between serum resistin levels and Larsen score for radiological joint damage in RA patients (p< 0.05). While Canoru et al 16 recorded that there was no significant correlation between resistin and ESR, and CRP.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary to our results, the studies conducted by Forsblad et al 19 , Kassem et al 15 and Rho et al 23 found a significant positive correlation between serum resistin levels and Larsen score for radiological joint damage in RA patients (p< 0.05). While Canoru et al 16 recorded that there was no significant correlation between resistin and ESR, and CRP.…”
Section: Discussioncontrasting
confidence: 99%
“…While Rho et al 23 reported that the concentrations of resistin did not differ significantly among patients with seropositive and seronegative RA. They also reported that disease duration, DAS 28, Larsen score, and CRP were not correlated with resistin.…”
Section: Discussionmentioning
confidence: 91%
“…It is widely accepted that leptin levels are elevated in patients with RA and that there is a correlation between serum leptin and synovial fluid/serum leptin ratio and disease duration and parameters of RA activity (Olama et al, 2010). Generally, leptin is considered to be pro-inflammatory, but this hormone has been also reported to reduce radiographic joint damage (Rho et al, 2009). This effect could be related to some leptin anabolic effects, such as the stimulation of the synthesis of insulin-like growth factor-1 (IGF-1) and transforming growth factor-(TGF-) at both the messenger RNA (mRNA) and protein levels (Dumond et al, 2003) The actions of leptin in RA are not only targeted to articular tissues, this adipokine also exerts direct modulatory effects on activation, proliferation, maturation and production of inflammatory mediators in a variety of immune cells, including lymphocytes, NK cells, monocytes/macrophages, dendritic cells, neutrophils and eosinophils (Lam & Lu, 2007).…”
Section: Leptinmentioning
confidence: 99%
“…In fact, patients with SLE have increased concentrations of leptin and these concentrations are associated with insulin resistance, BMI (Body Mass Index) and CRP (C-reactive protein) in these patients (Chung et al, 2009). …”
Section: Leptinmentioning
confidence: 99%
“…Adiponectin has been found to be higher in RA patients than in healthy controls (34,(77)(78)(79)(80)(81). Moreover, adiponectin levels are increased in early RA patients that had never taken disease-modifying antirheumatic drugs and in chronic RA patients (82).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 99%